Membagun Tradisi dan Strategi Enterpreneur Melalui Bisnis dan Gaya Hidup Pada Masyarakat Indonesia - Hafiza (Talenta Publisher, 2023)
Entrepreneurship is considered as a way out in overcoming the problem of limited employment opportunities and poverty faced by almost all countries, including Indonesia. This phenomenon occurs due to the low motivation and interest of the community to develop an entrepreneurial spirit (entrepreneurship). Based on this, Indonesia still needs to prepare drivers for economic development. The government in each country is obliged to encourage its young generation to build an entrepreneurial spirit, so that they are free from dependence on other parties. Recognizing the importance of working hard with the initial goal of self-prosperity, the field of entrepreneurship is an option that can be realized by all levels of society. The research method used in this study is a literature review and the results of the researchers' thinking. The type of data used is secondary data with a qualitative approach. However, it is realized that the process of becoming a successful entrepreneur is not an easy thing. So the need for entrepreneurial traditions and strategies through business and lifestyle in.